Non-performing loan and economic determinants in Asia-Pacific countries: evidence from credit card debt - Soh, Wei Ni (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Credit card loans are one of the NPL classified as doubtful requiring 50% provisioning and those which are more than 6 months in arrears should be classified as bad requiring 100% provisioning which has the high potential loss for banks when the users unable to pay back the amount. Country macroeconomics indicator leads to a rise in delinquency rates after controlling for credit supply and shocks like divorce and health coverage we investigate whether consumer propensity for delinquency and bankruptcy. The study sample consisted of 4 countries with 2 types of market classification which are developed countries by Singapore and Hong Kong, and emerging countries, Malaysia and Korea. A balanced panel regression shows unemployment rate play a significant variable to explain the NPL due to the credit card debt outstanding. The country development status helps in enhancing the reliability of the study.